Roles of technologies for future teaching in a pandemic: activity, agency, and humans-with-media - Villa-Ochoa, Jhony Alexander; Molina-Toro, Juan Fernando; Borba, Marcelo C. [UNESP] (Springer Nature, 2022)
Research literature on the role of mathematics teachers during the COVID-19 crisis shows that teacher preparation for emergency situations is required. In reporting on this exploratory study, we present and analyse lesson plans created by seven future teachers for mathematics classes during the pandemic. Data were collected between April and October 2021 from 16 four-hour class sessions in a Mathematics Degree Program at a public university in Medellín, Colombia. The notion of Humans-with-Media and the Learning by Expanding theory were used as frameworks to understand what roles prospective mathematics teacher (PMTs) assign to technologies for teaching in pandemic conditions. The PMTs’ uses of technology for teaching mathematics during a pandemic were categorized. The results show that technology was used to reorganize and reproduce mathematics teaching practices. This report addresses the impact of technology on the activity system, and we conclude with a discussion of opportunities and limitations of students’ conceptions about teaching and technology during a pandemic.
Keywords: Activity system; Agency; COVID-19; Humans-with-media; Technology